Cytotoxic Indolocarbazoles From a Marine-Derived Streptomyces Sp. OUCMDZ-5380 - Cui, Tongxu; Lin, Simin; Wang, Zizhen; Fu, Peng; Wang, Cong; Zhu, Weiming (Frontiers in Microbiology, 2022)
Under the guidance of GNPS molecular networking, three new indolocarbazoles named as streptocarbazoles F−H (1−3), along with staurosporine (4) were isolated from the marine-derived Streptomyces sp. OUCMDZ-5380. Structures of streptocarbazoles F−H were respectively determined as N-demethyl-N-hexanoylstaurosporine (1), N-(2-methyl-3-methoxypyridin-4-yl)-N-demethyl staurosporine (2), and 4-(N-demethylstaurosporine-N-yl)-1,2-dimethyl-3-methoxypyridinium (3) by spectroscopic analysis and ECD comparison with staurosporine. Compared with staurosporine (4), streptocarbazoles F−H (1−3) showed a selective antiproliferation of the acute myeloid leukemia cell line MV4-11 with the IC50 values of 0.81, 0.55 and 1.88 µM, respectively.